A rare case of foreign body aspiration presenting as subglottic stenosis: A case report. Issue 10 (23rd October 2021) - Paudel, Deepak; Dahal, Raunak; Sah, Bajarang Prasad; Chettri, Shyam Thapa; Gajurel, Pravid
Abstract: In rare cases, foreign body aspiration may present with similar clinical features and CT findings to subglottic stenosis. A high index of suspicion and additional diagnostic techniques may be required to distinguish them. Abstract : In rare cases, foreign body aspiration may present with similar clinical features and CT findings to subglottic stenosis. A high index of suspicion and additional diagnostic techniques may be required to distinguish them.